2016
DOI: 10.1038/srep21664
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-dependent kinase 2 protects podocytes from apoptosis

Abstract: Loss of podocytes is an early feature of diabetic nephropathy (DN) and predicts its progression. We found that treatment of podocytes with sera from normoalbuminuric type 1 diabetes patients with high lipopolysaccharide (LPS) activity, known to predict progression of DN, downregulated CDK2 (cyclin-dependent kinase 2). LPS-treatment of mice also reduced CDK2 expression. LPS-induced downregulation of CDK2 was prevented in vitro and in vivo by inhibiting the Toll-like receptor (TLR) pathway using immunomodulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 58 publications
1
27
0
Order By: Relevance
“…While TRAPP and COPII associate with SGs in undifferentiated podocytes in response to stress, this association was reduced in differentiated podocytes (Fig E). Of note, the proliferation to differentiation switch, as described (Saurus et al , ), is also accompanied by a decline in CDK activity (Fig F and G).…”
Section: Resultssupporting
confidence: 79%
“…While TRAPP and COPII associate with SGs in undifferentiated podocytes in response to stress, this association was reduced in differentiated podocytes (Fig E). Of note, the proliferation to differentiation switch, as described (Saurus et al , ), is also accompanied by a decline in CDK activity (Fig F and G).…”
Section: Resultssupporting
confidence: 79%
“…To define the reason for this, we investigated the expression of 3-phosphoinositide-dependent protein kinase 1 (PDK1) and cyclin-dependent kinase 2 (CDK2), both shown to induce apoptosis in podocytes when knocked down 17 , 18 . Interestingly, the expression of PDK1 was downregulated by 35% and CDK2 by 65% in CD2AP−/− podocytes when compared to wild type cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that PI3K/PTEN-PDK1 signalling in oocytes regulates the survival, loss, and activation of primordial follicles [24]. PDK1 is one of the activators of the Akt cell survival pathway and might be associated with the development of DKD through regulation of podocyte apoptosis [25,26]. The PDK1/Akt/mTOR pathway was activated both in diabetic rats and in human renal mesangial cells under high glucose condition [27].…”
Section: Discussionmentioning
confidence: 99%